2024
DOI: 10.1037/adb0000943
|View full text |Cite
|
Sign up to set email alerts
|

Applying behavioral economics to understand changes in alcohol outcomes during the transition to adulthood: Longitudinal relations and differences by sex and race.

Abstract: Objective: Population drinking trends show clear developmental periodicity, with steep increases in harmful alcohol use from ages 18 to 22 followed by a gradual decline across the 20s, albeit with persistent problematic use in a subgroup of individuals. Cross-sectional studies implicate behavioral economic indicators of alcohol overvaluation (high alcohol demand) and lack of alternative substance-free reinforcers (high proportionate alcohol-related reinforcement) as potential predictors of change during this d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 68 publications
(100 reference statements)
0
8
0
Order By: Relevance
“…The present study critically extends a sizeable body of cross-sectional literature [18,32] and initial longitudinal work [48,49] by providing a robust longitudinal examination of prospective and bidirectional associations between key behavioral economic indicators and alcoholrelated outcomes among a relatively large sample of emerging adults.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…The present study critically extends a sizeable body of cross-sectional literature [18,32] and initial longitudinal work [48,49] by providing a robust longitudinal examination of prospective and bidirectional associations between key behavioral economic indicators and alcoholrelated outcomes among a relatively large sample of emerging adults.…”
Section: Discussionmentioning
confidence: 75%
“…The present study critically extends a sizeable body of cross‐sectional literature [18,32] and initial longitudinal work [48,49] by providing a robust longitudinal examination of prospective and bidirectional associations between key behavioral economic indicators and alcohol‐related outcomes among a relatively large sample of emerging adults. The results revealed several relationships that were consistent with behavioral economic predictions [14,15], in addition to others that were less consistent or not supported.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Behavioral economic measures. The modi ed Activity Level Questionnaire measures past-month activity frequency and enjoyment with Likert scales and separate items for substance-related and substance-free activities (Acuff et al, 2023). The frequency and enjoyment ratings are multiplied to obtain a crossproduct score that re ects reinforcement derived from the activity.…”
Section: Secondary Outcomesmentioning
confidence: 99%
“…A recent daily diary study with non-student EA drinkers indicated that engagement in alternative enjoyable activities was the most frequently endorsed strategy to avoid drinking (Lau-Barraco & Linden-Carmichael, 2019). The Substance-Free Activity Session (SFAS) was developed to supplement alcohol-focused BAIs and uses MI, personalized normative feedback, goal setting, and an episodic future thinking exercise to target the behavioral economic mechanisms of substance-free reinforcement and delayed reward discounting (Acuff et al, 2023). The SFAS encourages EAs to identify and discuss the long-term bene ts associated with their life goals and to consider how their current patterns of time allocation and drinking (which are aggregated as personalized feedback) might impact those valued goals (Murphy et al, 2019) (Gex et al, 2023;Meshesha et al, 2020).…”
Section: Introductionmentioning
confidence: 99%